Answer:
9 x + 8 y = 10 (I)
y = -4x + 7 (II)
One way is to rewrite the second as
4x + y = 7
Now multiply this equation by 8
32 x + 8 y = 56
9 x + 8 y = 10 and now subtract the equations
23 x = 46 this gives x as 2
From equation (II) y = -4 (2) + 7 = -1
So our values are (2, -1)
Check:
(I) 9 x + 8 y = 10 9 * 2 - 8 = 10
(II) 4 x + y = 7 or 4 * 2 - 1 = 7
Or you can substitute equation (II) directly into equation (I)
Answer:
The remaining line is 1/2 of an inch
Step-by-step explanation:
3/4-1/4 will give you 2/4 which is easily simplified to 1/2
I hope this helps you :)
Answer:
x + 2, x ≠ -2
Step-by-step explanation:
Note that F(x) = x^2 + 4x + 4 factors into (x + 2)^2, and that we are dividing this by g(x) = x + 2. The quotient is x + 2, which in this problem has been named h(x).
The quotient (f/g)(x) is therefore x + 2 EXCEPT that this is not defined at x = -2, because the denominator, x + 2, will be zero there, undefined.